Active and assisted living : technologies and applications - Florez-revuelta, Francisco; Chaaraoui, Alexandros Andre (The Institution of Engineering and Technology, 2016)
This is a broad introductory handbook, covering the major technologies and applications in Ambient Assisted Living (AAL). The book focuses on current state-of-the-art technology and critical analysis, the applications of these technologies and also includes general issues such as usability, accessibility, privacy and ethics.
Keywords: Self-help devices for older people.; Older people with disabilities -- Care.; elektronické knihy; electronic books